An Array of Interconnected-opened-ended Multi Wall Carbon Nanotubes Grown on AAO Template - Hoa, Nguyen Duc; Hieu, Nguyen Van (Communications in Physics, 2012)
The uniform and high ordered array of interconnected-opened-ended multi wall carbon nanotubes (MWNTs) are synthesized into nanopores of anodic aluminum oxide (AAO) templates by thermal chemical vapor deposition (CVD) method without using metallic catalyst. The morphologies and quality of MWNTs are characterized by SEM, and Raman spectroscopy. The results show that at optimized growth conditions, the high quality interconnected-opened-ended MWNTs are successfully synthesized